Viabilidade e utilização em confeitaria de corantes naturais obtidos a partir da variedade de uva black magic, da beterraba e do mirtilo - Rosa, Juliano da (Universidade do Vale do Rio dos Sinos, 2018)
Dyes are substances added to foods and beverages, in order to confer or intensify the color of the product, making it more attractive. Usually, artificial dyes are used for both the lower cost of production and greater stability over the natural ones. The search for healthier living standards causes industries to seek new alternatives to serve the market. This work will seek to evaluate the viability of confectionery of natural dyes obtained by lyophilization of the variety of black magic grape, beet and blueberry, replacing the artificial dyes. For this, the products were prepared, lyophilized and tested in the confectionery by means of their addition to the French meringue; °Brix test; color analysis and sensory testing. For the triplicate samples of beet, blueberry and grape °Brix, values of 5,92, 8,52 and 15,17 °Brix respectively were obtained, thus the beet has the lowest amount of sugar among the products. With regard to color, all products were satisfactory, with color intensified proportionally, as the dye contraction increases. The sensorial test, the beet given its accentuated characteristic taste, becomes impractical for application in the confectionery. Thus, among the evaluated dyes: black magic grape, beet and blueberry, only those of grape and blueberry have general satisfactory characteristics to their use in the confectionery, it is emphasized however that additional studies are necessary regarding the adequacy of the conditions of processing, storage, determination of maximum permissible concentrations, these being the most critical points of production.
Keywords: Corante alimentar; Corante natural; Uva; Beterraba; Mirtilo; Food coloring; Natural coloring; Grape; Beet; Blueberry; ACCNPQ::Ciências da Saúde::Nutrição